(3RgQI GdMOjbI aj Yde GdehSjbis - (3SYhOj EHQGgje GdeUQj GdTGaYjs ((3SdjeGf aQM Hf eMeO aQM GdTGaYi s)
(3ChdgG (B:s
(3hHYO SejJgG HRgQI GdMOjbI VefJgG bhGYO GdehSjbi s
(3BNQgG (B:s
(3hdG JLYd GdOfjG CcHQ gefG hdG eHdZ YdefG s
(3HgG fXGe GdJYbjHIs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3ehSjbi JjehQ (B44) s
Keywords: (3GdehSjbi hGdZfGAs